1981
DOI: 10.1266/jjg.56.193
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome elimination in different meristematic regions of hybrids between Hordeum vulgare L. and H. bulbosum L..

Abstract: Cytological observations were made on spike primordia as well as root and leaf meristems of hybrids between Hordeum vulgare and H, bulbosum (2x) to elucidate mechanism of chromosome elimination. High frequencies of cells with micronuclei were observed in spike primordia of the hybrids examined. The average percentages of cells with micronuclei in three different hybrids were 16.8% (R25788), 12.9% (S92-201) and 7.9% (5130-200). About 40% of spike primordium cells of R25788 had fewer chromosomes than the 14 expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The well-understood and well-explored examples are found in crosses between Hordeum species, especially in those involving H. bulbosum (Davies 1974;Orton and Tai 1977;Jorgensen and Bothmer 1988;Linde-Laursen and Bothmer 1993). The elimination rate of H. bulbosum chromosomes is tissue-dependent (Noda and Kasha 1981) and affected by the physiological conditions of cells, such as growth temperature of hybrid embryos and tissue culture conditions of hybrid meristems (Pickering 1985;Noda and Takayama 1986). The gradual and selective elimination of H. bulbosum chromosomes in interspecific hybrids is attributed to chromosome fragmentation, micronucleus formation and chromatin degradation (Subrahmanyam and Kasha 1973;Thomas 1988), lagging chromosomes and bridges, noncongregated chromosomes at metaphase, or the failure of chromosome migration to anaphase poles (Bennett et al 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The well-understood and well-explored examples are found in crosses between Hordeum species, especially in those involving H. bulbosum (Davies 1974;Orton and Tai 1977;Jorgensen and Bothmer 1988;Linde-Laursen and Bothmer 1993). The elimination rate of H. bulbosum chromosomes is tissue-dependent (Noda and Kasha 1981) and affected by the physiological conditions of cells, such as growth temperature of hybrid embryos and tissue culture conditions of hybrid meristems (Pickering 1985;Noda and Takayama 1986). The gradual and selective elimination of H. bulbosum chromosomes in interspecific hybrids is attributed to chromosome fragmentation, micronucleus formation and chromatin degradation (Subrahmanyam and Kasha 1973;Thomas 1988), lagging chromosomes and bridges, noncongregated chromosomes at metaphase, or the failure of chromosome migration to anaphase poles (Bennett et al 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The selective elimination of the chromosomes of one of the parental genotypes may be associated with disturbances in nuclear division (such as noncongressed chromosome at metaphase, lagging chromosomes and bridges at anaphase, chromatin fragments, degraded type of chromatin, multipolar spindles and micronuclei) in hybrid embryos and endosperm (Lange 1971;Bennett et al 1976). According to Noda and Kasha (1981) the failure of congregation of some chromosomes during prometaphase appears to be main mitotic disturbance leading to chromosome elimination in hybrids between Hordeum vulgare and H. bulbosum. Gupta (1969) suggested that significant difference between the S and G2 periods of the parental species might lead to elimination of a chromosome segments or the whole genome of the species having the longer S or G2 phases.…”
Section: Chromosome Constitutions Of 'Elatior'-begonia Hybridsmentioning
confidence: 99%
“…The several Ax-3jc mosaics support this possibility. Evidence is accumulating that interspecific hybrids, new amphidiploids, and new auto polyploids tend to be mitotically unstable (4,5,13,16,17,20,21,23,25,30). Chromosome loss during mitosis can result in aneusomaty or haploidy (23,24,25) or in production of gametes with unexpectedly low chromosome numbers.…”
Section: > • '/mentioning
confidence: 99%
“…Evidence is accumulating that interspecific hybrids, new amphidiploids, and new auto polyploids tend to be mitotically unstable (4,5,13,16,17,20,21,23,25,30). Chromosome loss during mitosis can result in aneusomaty or haploidy (23,24,25) or in production of gametes with unexpectedly low chromosome numbers. Britton and Hull (4, 5), for example, found that the tetraploid blackberry cultivar 'Eldorado' produced a mixture of 2jc, 4jc, and 6x seedlings when selfed and a mixture of 2jc and 3x hybrids when crossed with 2x raspberry.…”
Section: > • '/mentioning
confidence: 99%